Benefit-risk associated with the consumption of fish bycatch from tropical tuna fisheries. (December 2020) - Sardenne, Fany; Bodin, Nathalie; Médieu, Anaïs; Antha, Marisa; Arrisol, Rona; Le Grand, Fabienne; Bideau, Antoine; Munaron, Jean-Marie; Le Loc'h, François; Chassot, Emmanuel
Abstract: Mercury, omega-3 (docosahexaenoic acid, DHA and eicosapentaenoic acid, EPA) and macronutrients (fat and proteins) were quantified on a wet weight (ww) basis in 20 species of fish taken as bycatch in tropical tuna fisheries. Based on a hazard quotient taking into account mercury and omega-3 contents, a benefit-risk assessment for the consumption of these pelagic species was conducted for three people categories: young children, children and adults. All fish bycatch were found to be an excellent source of proteins (min‒max = 14.4–25.2 g/100 g fillet), had low omega-6/omega-3 ratios (<1, except for silky shark), and had mercury content below the safety limits defined by sanitary agencies. Silky shark and Istiophoridae had the highest mercury contents (min‒max = 0.029–0.317 ppm ww). Omega-3 contents were the lowest in silky shark (0.2 ± 0.2 mg/100 g fillet) and the highest in striped marlin (3.6 ± 3.2 g/100 g fillet). Billfishes (Istiophoridae, including striped marlin), minor tunas (Scombridae), and Carangidae had the highest omega-3 contents (min‒max = 0.68–7.28 g/100 g fillet). The highest hazard quotient values obtained for silky shark and great barracuda reflected a lower nutritional benefit (i.e., low omega-3 source) than risk (i.e., mercury exposure), making them not advisable for consumption. Eight species had low hazard quotients, and among them cottonmouth jack and flat needlefish were found of high health interest (high protein, moderate fat contents, and low omega-6/omega-3 ratio). A daily serving portion of 85–200 g (according to people category) can be recommended for these species. Batfish, and to a lower extent pompano dolphinfish and brassy chub, can also be consumed safely and would provide greater health benefits than risks. These results advocate for a better access of these species to local populations. Graphical abstract: Image 1 Highlights: Mercury and omega-3 were quantified in 20 fish species from tuna fisheries bycatch. All species are good protein sources, with low omega-6/omega-3 ratio. Eight species are of high interest, especially cottonmouth jack and flat needle fish. Silky shark and great barracuda are not advised for consumption (low omega-3, high mercury). Abstract : Based on omega-3, fat, protein, and mercury contents, most fish bycatch from tuna fisheries would be good food sources to reduce nutritional insecurity for local populations.